Gender Estimation in Anatolian Population from Scapula Measurements Using Volume Rendering Technique with 3D Computerized Tomography - Tetiker, Hasan; Gençer, Ceren Uğuz (The Bulletin of Legal Medicine, 2020)
Objective: The aim of this study is to evaluate the sexual dimorphism of the scapula and to measure the accuracy of the results of the measurements performed by computed tomography imaging of the thorax for gender estimation in the modern Anatolian population.Materials and Methods: Multidetector CT images of 302 cases (164 males, 138 females) with ages between 20 and 93 and taken between February 2019 and April 2019 in Radiology Department of Muğla Sıtkı Koçman University Training and Research Hospital were used. Longitudinal lengths (LU), transverse lengths (TU), and spina scapula lengths (SSU) of the right and left side scapulae were measured and evaluated. The effect of measurements on gender determination was determined by Logistic Regression analysis.Results: Scapula measurements were higher in males than in females (p
Keywords: forensic anthropology; sex estimation; scapula; multidetector computed tomography; sexual dimorphism